ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRICS "MAKE IT RIGHT" AND "PERMISSION TO DANCE" BY BTS - Agustina, Adilia Eka; Mustikawati, Yunitari (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
This study's purpose is to examine the kinds of figurative language and the meaning contained in the figurative language contained in the lyrics of the songs "Make It Right" and "Permission to Dance", with reference to Griffiths (2006) on semantics for meaning and Knickerbocker and Renninger's (1963) theoretical framework for figurative language. The researcher used a descriptive qualitative method in conducting this research. The researcher found five types of figurative language and their meanings contained in the lyrics of the songs "Make It Right" and "Permission To Dance," namely: metaphor, simile, personification, hyperbole, and alliteration. The two types of figurative language most commonly used by researchers are metaphor and simile. Based on the data obtained, 4 metaphors, 4 similes, 3 personifications, 2 hyperboles, and 1 alliteration were found. The most dominant figurative languages are metaphor and simile. The meanings of these two songs are very different; it can also be seen that these two songs have a different atmosphere even though the type of music is almost the same, namely R&B remixes. In the song "Make It Right," they (BTS) are telling the beginning of their career journey, which previously was that of ordinary singers that not many people knew about. While the song Permission to Dance encourages fans to remain optimistic in the midst of a worldwide pandemic.